Chemical composition and biological activities of Artemisia judaica essential oil from southern desert of Jordan. (15th September 2016) - Abu-Darwish, M.S.; Cabral, C.; Gonçalves, M.J.; Cavaleiro, C.; Cruz, M.T.; Zulfiqar, Ali; Khan, I.A.; Efferth, T.; Salgueiro, L.
Abstract: Ethnopharmacologic relevance: Artemisia judaica L. (Arabic name: Beithran ), is a medicinal and aromatic plant growing in the valley bottoms of desert areas, particularly in the southern desert of Jordan nearest to the Jordan-Saudi Arabia borders and in Wadi Araba in the Southern Badia. In Jordan, A. judaica is widely used in traditional medicine being recommended by aboriginal Bedouins in the North Badia region of Jordan as calmative. Furthermore, it is used for the treatment of stomach ache, heart diseases, sexual weakness, diabetes, gastro-intestinal disorders and external wounding. Additionally, other folk medicines of the Arabic region commonly use this aromatic plant for the treatment of inflammatory-related diseases, for instance fungal infections, diabetes, atherosclerosis, cancer and arthritis. Aim of the study: Considering the traditional medicinal uses and the lack of scientific studies addressing the cellular and molecular mechanisms behind A. judaica claimed activities, the present study was designed to validate some of the traditional uses ascribed to this species, specifically the antifungal and anti-inflammatory activities of A. judaica essential oil at doses devoid of cytotoxicity to mammalian cells. Materials and methods: Chemical analysis of A. judaica essential oil isolated by hydrodistillation from aerial parts was carried out by gas chromatography (GC) and gas chromatography–mass spectrometry (GC–MS). The antifungal activity (minimal inhibitory concentrations and minimal lethal concentrations) was evaluated against yeasts, dermatophyte and Aspergillus strains. In order to deeply explore the mechanisms behind the anti-fungal effect of the essential oil, the germ tube inhibition assay and the biofilms formation assay were evaluated using Candida albicans . The assessment of cell viability was accomplished using the 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide (MTT) assay in both hepatocytes and macrophages. Furthermore, the in vitro anti-inflammatory potential of A. judaica oil was evaluated by measuring nitric oxide (NO) production using lipopolysaccharide (LPS)-stimulated mouse macrophages. Results: Oxygen containing monoterpenes are a representative group of constituents (68.7%) with piperitone (30.4%), camphor (16.1%) and ethyl cinnamate (11.0%) as main compounds. The highest antifungal activity of the oil was observed against Cryptococcus neoformans, with a MIC value of 0.16 µL/mL. The oil revealed an important inhibitory effect on germ tube formation in C. albicans with 80% inhibition of filamentation at a concentration of 0.16 µL/mL. Importantly, the oil also interfered with pre-formed biofilms by reducing the amount of the attached biomass. Furthermore, the essential oil significantly inhibited NO production evoked by LPS on macrophages at concentrations with very low toxicity (0.32 µL/mL) or without toxicity (0.16 µL/mL) to both macrophages and hepatocytes. Conclusions: The present study revealed that A. judaica essential oil from Jordan significantly inhibited germ tube formation and disrupted preformed biofilms of C. albicans, emphasizing the therapeutic potential for the treatment of disseminated candidiasis. Additionally, safe concentrations of this essential oil significantly inhibited NO production elicited by LPS in macrophages, highlighting its potential anti-inflammatory activity. Overall, A. judaica bears promising therapeutic potential for further drug development. Importantly, this work also validates some of the traditional uses of A. judaica. Graphical abstract: